Comparison of Various Irrigation Techniques for the Removal of Silicone Oil-Based Calcium Hydroxide Intracanal Medicament from the Apical Third: An SEM Study - Saji, Shalin Ann; Shetty, Chitharanjan; Kaur, Gurmeen; Bajpe, Sunheri; Chandraprabha, Chandraprabha; Shroff, Rashi; Qaiser, Shazeena; Gupta, Surabhi (Journal of Health and Allied Sciences NU, 2024)
Objective To evaluate the efficacy of various irrigants (5.25% sodium hypochlorite [NaOCl] followed by 17% ethylenediaminetetraacetic acid [EDTA] and 0.2% chitosan nanoparticle [NP]) and different irrigation techniques (conventional and EndoVac) for the removal of Metapex from the apical third of the root canal by scanning electron microscopy (SEM) analysis.Materials and Methods Forty extracted single-rooted human premolars were instrumented using a rotary ProTaper file system up to F3. The canals were dried and Metapex was placed inside the root canal. The access cavity was sealed with a cotton pellet and Cavit followed by the storage of specimens at 37°C at 100% humidity for 1 week. Cavit was removed and the samples were divided into: Group 1 (conventional irrigation using 5.25% NaOCl and 17% EDTA, n = 10), Group 2 (conventional irrigation using 0.2% chitosan NP, n = 10), Group 3 (EndoVac using 5.25% NaOCl and 17% EDTA, n = 10), and Group 4 (EndoVac using 0.2% chitosan NP, n = 10). After irrigant activation, the roots were divided in half, and the apical third of one-half of each tooth was subjected to SEM analysis. A five-graded scoring scale was used to evaluate dentinal wall cleanliness. Data were statistically analyzed using one-way analysis of variance.Results There were statistically significant differences in mean canal cleanliness scores observed between the four groups. Chitosan NPs showed lower mean canal cleanliness scores at the apical one-third of the root canal indicating better cleanliness when compared with the other irrigants and techniques.Conclusion None of the irrigation techniques was successful in entirely removing the calcium hydroxide intracanal medicament from the apical third.
Keywords: calcium hydroxide; cetrimide; chitosan; EndoVac; intracanal medicament